Preface - Jörges, Sven; Saay, Salim; Smyth, Steven (Electronic Communications of the EASST, 2025)
Established in 2004, the International Symposium on Leveraging Applications of Formal Methods, Verification and Validation (ISoLA, see http://isola-conference.org), serves as a platform for researchers, practitioners and users from engineering and other disciplines, for sharing ideas and approaches concerning the specification, analysis, verification, certification, construction, testing, and maintenance of software systems, considering their respective application domains. In 2014, ISoLA introduced the Doctoral Symposium as an integral part of the conference to provide a scientific and networking opportunity for young academics. Besides the thematically focused tracks of the main event, the Doctoral Symposium successfully created a space for Master and PhD students to share their research ideas and projects, to discuss them with the scientific community and to expand their networks and collaborations. The sessions include high-quality works covering a broad range of topics, being well-received by the young attendants as well as by participating senior researchers. In 2024, the Doctoral Symposium expanded to include contributions from participants of AISoLA, thus broadening the scope to encompass a more diverse range of topics by integrating recent advances in AI. This volume comprises the post-proceedings of the 2024 Doctoral Symposium. It contains six papers that have been selected as the result of a thorough review process. As the organizers of the Doctoral Symposium, we thank all reviewers who invested a lot of time and effort in this process. Your valuable and intensive feedback has contributed to the high quality of the papers in this volume. The organizers of the 2024 (A)ISoLA Doctoral Symposium, Sven Jörges, Salim Saay and Steven Smyth Volume Reviewers • Sowelu Avanzo, University of Torino, Italy • Ursula Coester, Westphalian University of Applied Science, Germany • Sven Jörges, Dortmund University of Application Sciences and Arts, Germany • Daniel Sami Mitwalli, University of Limerick, Ireland • Sonja Niemann, Bavarian Research Institute for Digital Transformation, Germany • Salim Saay, University of Limerick, Ireland • Jonas Sch¨ürmann, TU Dortmund, Germany • Steven Smyth, TU Dortmund, Germany • Sebastian Teumert, University of Limerick, Ireland